2021
DOI: 10.3390/joitmc7020162
|View full text |Cite
|
Sign up to set email alerts
|

Research Institutes in Poland as an Element of the National Innovation System—Complexity, Financing and Effectiveness

Abstract: Transfer and diffusion of knowledge and technology is a key condition for the development of innovation. In practice, they take place at the interface between science and business, which makes the level of innovation and development of a given economy depend on the effectiveness and efficiency of universities and other scientific units co-creating the national innovation network. With this important circumstance in mind, this article presents an assessment of the operations of selected research institutes in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 102 publications
(168 reference statements)
0
1
0
Order By: Relevance
“…It is necessary to find indicators of bankruptcy of small innovative enterprises that receive preferential loans from development institutions, identify trend, seasonal and cyclical components and, rejecting the random component, carry out forecasting and frequency analysis of crisis phenomena in the supply and demand market for scientific knowledge. Existing works [15,30] are based on specific indicators that are either not calculated at all or calculated using exclusive methods. The inability of a small innovative enterprise to restore solvency within the established period of the development institution is considered as bankruptcy.…”
Section: Methodsmentioning
confidence: 99%
“…It is necessary to find indicators of bankruptcy of small innovative enterprises that receive preferential loans from development institutions, identify trend, seasonal and cyclical components and, rejecting the random component, carry out forecasting and frequency analysis of crisis phenomena in the supply and demand market for scientific knowledge. Existing works [15,30] are based on specific indicators that are either not calculated at all or calculated using exclusive methods. The inability of a small innovative enterprise to restore solvency within the established period of the development institution is considered as bankruptcy.…”
Section: Methodsmentioning
confidence: 99%
“…Jonek-Kowalska, I believes that the transfer and diffusion of knowledge and technology is a key condition for the development of innovation, and the level of innovation and the degree of development depends on the effectiveness and efficiency of the scientific units of the university and regional innovation network, so promoting innovation transformation can accelerate the transformation of basic scientific research results to the practical application level [12]. Li, W and Zhang, P used the Data Envelopment Analysis (DEA) ) method to measure the transformation efficiency of EMI scientific and technological achievements and found that with the optimization of industrial structure, the energy consumption and carbon emission of the industry improved, and scientific innovation is the cornerstone of the optimization of industrial structure [13].…”
Section: Introductionmentioning
confidence: 99%
“…A number of publications are devoted to the study of the interdependence between business, creative innovations (Galuk et al, 2016;Nanni and Santos, 2018;Gouvea et al, 2021). The effectiveness of financing creative innovations has been considered in the works of scientists from different parts of the world (Cunningham et al, 2008;Kasych and Kanunikova, 2016;Fazlagić and Skikiewicz, 2019;Eprianti and Firdaus, 2020;Jonek-Kowalska, 2021). The performance of digital financial innovations (DFI) has been studied by scholars from the UAE (Hussain and Papastathopoulos, 2022).…”
mentioning
confidence: 99%